2016
DOI: 10.1080/09638288.2016.1215559
|View full text |Cite
|
Sign up to set email alerts
|

Changes in return to work among patients in vocational rehabilitation: a self-determination theory perspective

Abstract: These results underscore the importance of health care practitioners' providing support for their patients' autonomy, competence, and relatedness to improve well-being, physical activity, and RTW in the context of vocational rehabilitation. Implications for Rehabilitation Vocational rehabilitation that emphasizes physical activity is associated with increases in patients' well-being, physical activity, and return to work (RTW). It is important for health care practitioners to provide support for their patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 43 publications
1
31
0
1
Order By: Relevance
“…Interestingly, no differences on personal and work characteristics were observed when comparing trajectories with and without relapse. The finding that these trajectories did not differ on demographical factors, type of MHP or work context characteristics suggests that differences between trajectories with and without relapse may be explained by psychological and human work-related factors (eg, supervisor behaviour, sense of control, general working conditions) 29–32. Importantly, this would imply that relapse depends on factors that can be influenced to a certain extent.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, no differences on personal and work characteristics were observed when comparing trajectories with and without relapse. The finding that these trajectories did not differ on demographical factors, type of MHP or work context characteristics suggests that differences between trajectories with and without relapse may be explained by psychological and human work-related factors (eg, supervisor behaviour, sense of control, general working conditions) 29–32. Importantly, this would imply that relapse depends on factors that can be influenced to a certain extent.…”
Section: Discussionmentioning
confidence: 96%
“…Future research may investigate whether OPs recognise the different RTW trajectories and how knowledge about different trajectories affects treatment decisions (eg, using focus groups). Since no differences between trajectories with and without relapse were found on the characteristics included in this study, future studies may examine whether trajectories differ on psychological and human work-related characteristics such as RTW self-efficacy,33 experienced autonomy over the RTW process,29 frequency and timing of communication between different stakeholders30 31 and psychosocial work environment 32. To study this, it is highly relevant for OHS to start recording these factors systematically in collaboration with researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicated that poor oral health status and poor OHRQoL were associated with poor general well‐being and quality of life in some settings; however, further evidence is needed to support this interpretation (Naito et al, ). General well‐being involves positive experiences at both the physical and psychological levels, and has been operationalized by vitality, absence of anxiety, and absence of somatic symptom burden (Baard, Deci, & Ryan, ) and by positive affect, vitality, absence of negative affect, and absence of somatic symptom burden (Farholm, Halvari, Niemiec, Williams, & Deci, ). In the dental field, poor OHRQoL has been associated with poor general health and well‐being (Buunk‐Werkhoven et al, ; Halvari, Halvari, Bjørnebekk, & Deci, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, intrinsic motivation is reduced when the health professionals may take motivation for granted, even if the patient has essential unmet basic needs ( Hardcastle et al , 2015 ). The basic needs for competence, autonomy and relatedness must be met to support well-being, optimism and motivation ( Farholm et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%